Treatment results of respiratory distress syndrome in preterm infants at the pediatric center of Hue Central Hospital - Hao, Tran Kiem; Trinh, Nguyen Thi Thao; Dien, Nguyen Van; Linh, Hoang Mai (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Acute respiratory distress syndrome (ARDS) in premature infants is one of the leading causes of death. Surfactant replacement therapy has been the mainstay of treatment for preterm infants with RDS. This study aimed to evaluate the results of surfactant therapy for premature infants with RDS at the Pediatric Center of Hue Central Hospital. Methods: A prospective, descriptive, and comparative study was conducted on 52 preterm infants with RDS based on clinical and chest radiographic findings before and after intervention. All infants received conventional surfactant therapy or INSURE. Evaluation of treatment results after 6 hours based on: SpO2, FiO2, a/APO2, and chest X-ray. Results: Surfactant treatment markedly reduced the need for FiO2 and Surfactant treatment markedly reduced FiO2. requirement and improved SpO2. The average SpO2 of 91.15% increased to 95.67%. The average FiO2 of 51.54% decreased to 40.5%. Lung lesions on X-ray have markedly improved after treatment, as shown in the improvement of lesions. Alveolar and arterial oxygen rates (a/APO2) improved significantly after surfactant administration. 33/52 (63.5%) cases eventually improved within 6 hours after treatment without any complications. Conclusion: A surfactant replacement that counterbalances surfactant inactivation seems to improve oxygenation and lung function in many preterm infants with respiratory distress syndrome without any apparent negative side effects.